Genetic Characteristics of Human Parainfluenza Virus Types 1–4 From Patients With Clinical Respiratory Tract Infection in China - Shao, Nan; Liu, Bo; Xiao, Yan; Wang, Xinming; Ren, Lili; Dong, Jie; Sun, Lilian; Zhu, Yafang; Zhang, Ting; Yang, Fan (Frontiers in Microbiology, 2021)
Human parainfluenza viruses (HPIV1–4) cause acute respiratory tract infections, thereby impacting human health worldwide. However, there are no current effective antivirals or licensed vaccines for infection prevention. Moreover, sequence information for human parainfluenza viruses (HPIVs) circulating in China is inadequate. Therefore, to shed light on viral genetic diversity and evolution, we collected samples from patients infected with HPIV1–4 in China from 2012 to 2018 to sequence the viruses. We obtained 24 consensus sequences, comprising 1 for HPIV1, 2 for HPIV2, 19 for HPIV3, and 2 for HPIV4A. Phylogenetic analyses classified the 1 HPIV1 into clade 2, and the 2 HPIV4 sequences into cluster 4A. Based on the hemagglutinin-neuraminidase (HN) gene, a new sub-cluster was identified in one of the HPIV2, namely G1c, and the 19 HPIV3 sequences were classified into the genetic lineages of C3f and C3a. The results indicated that HPIV1–4 were co-circulated in China. Further, the lineages of sub-cluster C3 of HPIV3 were co-circulated in China. A recombination analysis indicated that a putative recombination event may have occurred in the HN gene of HPIV3. In the obtained sequences of HPIV3, we found that two amino acid substitution sites (R73K in the F protein of PUMCH14028/2014 and A281V in the HN protein of PUMCH13961/2014) and a negative selection site (amino acid position 398 in the F protein) corresponded to the previously reported neutralization-related sites. Moreover, amino acid substitution site (K108E) corresponded to the negative selection site (amino acid position 108) in the 10 F proteins of HPIV3. However, no amino acid substitution site corresponded to the glycosylation site in the obtained HPIV3 sequences. These results might help in studying virus evolution, developing vaccines, and monitoring HPIV-related respiratory diseases.